Numerical Investigation of Rotating Instability Development in a Wide Tip Gap Centrifugal Compressor - Xavier Flete; Nicolas Binder; Yannick Bousquet; Sandrine Cros (International Journal of Turbomachinery, Propulsion and Power, 2023)
In the current study, full-stage unsteady simulations were performed to investigate rotating instability inception mechanisms in a particularly large tip clearance centrifugal compressor with a vaneless diffuser and a volute. Four operating points along a speed line were analysed to understand the influence of the mass flow reduction on flow structures. Close to the peak efficiency, an unsteady interaction between the tip clearance vortices and splitter blades was observed. Considering other studies, the influence of the tip gap size was analysed. Then, a large-scale vortex shedding from the leading edges of the main blades was detected when the stage operated near the maximum pressure ratio. It was demonstrated that shed vortices were caused by the combination of the radial gradient of the tangential velocity under the tip vortex and the reverse backflow near the casing. Previous studies on axial compressors refer to these vortical structures as backflow vortices. These vortices cause a significant increase in the incidence angle in the tip region.